In vitro Pharmacokinetics/Pharmacodynamics Evaluation of Fosfomycin Combined with Amikacin or Colistin against KPC2-Producing Klebsiella pneumoniae - Yu, Wei; Zhou, Kai; Guo, Lihua; Ji, Jinru; Niu, Tianshui; Xiao, Tingting; Shen, Ping; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2017)
OBJECTIVES: The emergence of carbapenem-resistant Enterobacteriaceae, especially Klebsiella pneumoniae, has become a major concern in clinic settings. Combination therapy is gaining momentum to counter the secondary resistance and potential suboptimal efficacy of monotherapy. The aim of this study was to evaluate the bactericidal effect of fosfomycin (FM), amikacin (AMK) or colistin (COL) alone and combinations against KPC2-producing K. pneumoniae using dynamic model by simulating human pharmacokinetics in vitro. METHODS: The Pharmacokinetics Auto Simulation System 400 system was employed to simulate different dosing regimens of FM, AMK and COL alone and combination. Bacterial growth recovery time (RT) and the area between the control growth and antibacterial killing curves (IE) were used as unbiased and comprehensive means for determining the antimicrobial effect. RESULTS: We observed that COL alone was much pronounced than FM or AMK against KPC-Kp. IE of FM (8 g every 8 hours) plus AMK (15 mg/kg once-daily) and FM (8 g every 8 hours) plus COL (75,000 IU/kg every 12 hours) were higher (>170 and >200 LogCFU/mL•h-1, respectively) than that of monotherapies against sensitive strains. Of note, the rate of resistance was lower when using the combination of FM (8 g every 8 hours) plus COL (75,000 IU/kg every 12 hours) than using COL (75,000 IU/kg every 12 hours) alone. CONCLUSIONS: The combination of FM (8 g every 8 hours) plus AMK (15 mg/kg once-daily) and FM (8 g every 8 hours) plus COL (75,000 IU/kg every 12 hours) were effective at maximizing bacterial killing and suppressing emergence of resistance.